THE MEDIATING ROLE OF SIPD IN GOVERNANCE AND FINANCIAL REPORTING QUALITY IN LOCAL GOVERNMENT - Moh. Halim Halim; Riyanto Setiawan Suharsono; Ahmad Izzuddin (JAT : Journal Of Accounting and Tax, 2026)
This study examines the impact of government governance on the quality of financial reporting, considering both direct effects and indirect effects through the adoption of the Regional Government Information System (SIPD). It integrates Good Governance theory with the Technology Acceptance Model within a local government context. Data were collected using a structured questionnaire from 120 employees at the Bondowoso Regency Education Office who were involved in financial management, selected through purposive sampling. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Results indicate that governance significantly influences SIPD implementation and directly improves reporting quality, while SIPD implementation itself strongly enhances reporting quality. The significant indirect effect of governance through SIPD indicates partial mediation, accounting for 57.2% of the total effect, suggesting that SIPD serves as a crucial transmission mechanism rather than merely a technological tool. Local governments should pursue governance reforms alongside digital investments; SIPD administrators should focus on system stability, module integration, and staff training. Additionally, the Inspektorat Daerah and the Badan Pengelola Keuangan Daerah should strengthen independent audits and standardize reconciliation processes. By conceptualizing SIPD as a mediator rather than a direct predictor of reporting quality and expanding the Technology Acceptance Model from individual to organizational levels, this research clarifies the institutional and technological pathway linking governance and reporting quality in a decentralized, moderate-capacity regency.